KRITIK TERHADAP TEORI ḤUDŪD MUHAMMAD SYAHRUŔ DAN IMPLEMENTASINYA DALAM AYAT- AYAT HUDŪD - Abdul Rasyid Ridho (UIN Mataram, 2018)
The existence of the ḥudūd theory is due to the thoughtlessness of the ummah which is marked by the dependence of all legal problems on their priests. What was conveyed by the previous ulamas still held firm without trying to conduct a review, whether his opinion was still relevant to current conditions. This is what causes Islamic law can not develop as the times progress. Therefore Muhammad Syahrūr abolished the ability of previous scholars to think by offering the concept of ḥudūd (boundary theory). For Syahŕ ther law must be Ş instead of li kulli zamān wa then (the law must be applicable in every time and place